156 Where to Draw the Line: Understanding Preferences in Mucosal Collar Length After Circumcision. Issue 1 (1st April 2022) - Callegari, M.; Muncey, W.; Kim, T.; Rhodes, S.; Woo, L.; Hannick, J.
ABSTRACT: Introduction: Male circumcision is a polarizing and omni prevalent procedure within the United States (U.S.). Little understanding exists regarding patient preferences for circumcision appearance. Objective: To illicit how mucosal collar length may be perceived in terms of overall cosmesis and desirability amongst adults. Methods: A questionnaire using REDCap was created and distributed through Amazon Mechanical Turk. Respondents provided demographic information and circumcision status before being challenged with artistic representations of circumcised penises with increasing lengths of mucosal collar. Participants were asked to select the most and least aesthetically pleasing image as well as rate the "importance of appearance" from 0 to 100. Responses were analyzed with ordinal regression models. Results: Preference for shorter mucosal collars were seen in respondents with a postgraduate education (P = 0.013) and no religious affiliation (P = 0.034). In contrast, participants reporting a religious affiliation preferred longer mucosal collars (P = 0.034). Circumcised males rated appearance as being more important (P = 0.001) in contrast to uncircumcised males who did not (P = 0.001). Women were neutral (P = 0.199). Black or African American participants valued circumcision appearance more (P = 0.020) than Caucasian participants (P = 0.021). Conclusions: Preferences regarding mucosal collar length appear to be influenced by education and religion. Overall, our study did not observe a predominant preference for mucosal collar length following circumcision. With this in mind, surgeons should engage patients preoperatively in discussions regarding preferences and desired cosmetic outcomes. Disclosure: No